Penguatan Kapasitas Mahasiswa dalam Meningkatkan Kesadaran Hak Asasi Manusia di Era Digital - M. Yunasri Ridhoh; Sri Astuti Nasir; Indri Iswardhani; Nur Fadilah Ayu Sandira; Nulthazam Sarah (Manfaat : Jurnal Pengabdian Pada Masyarakat Indonesia, 2026)
The rapid development of digital technology has brought significant changes to social life, particularly among university students as an educated group and agents of change. On the one hand, digital spaces provide opportunities for freedom of expression and public participation; on the other hand, they also present various challenges related to Human Rights (HR), such as privacy violations, the spread of hate speech, disinformation, and cyberbullying. These conditions highlight the importance of strengthening students’ capacity to ensure they possess adequate understanding and awareness of human rights values in the digital era. This community service article aims to enhance students’ human rights awareness through capacity-building activities conducted within the university environment. The service method was implemented through educational activities in the form of seminars, material presentations, and interactive discussions addressing fundamental human rights concepts, digital ethics, privacy protection, and responsible freedom of expression.The results of the activities indicate an increase in students’ understanding and awareness of human rights issues in the digital era, as well as the development of more critical and ethical attitudes in utilizing digital spaces. This initiative also strengthened the synergy between higher education institutions and the government in promoting human rights awareness among students. Overall, this community service activity makes a positive contribution to strengthening students’ capacity to face human rights challenges in the digital era.